STUDY OF CONCRETE FILLERS TO IMPART SPECIAL QUALITIES TO THE ROAD SURFACE (ROAD SURFACE) TO ENSURE SAFE ROAD TRAFFIC - Colonel K. K. Rapikov (Web of Journals Publishing, 2023)
The article presents proposals for the introduction of polymer-based sulfur concrete using innovative approaches to ensure the construction of roads with high-quality road surface. In this way, a reduction in road accidents will be achieved.
Keywords: safety, sulfur concrete, road, road surface, concrete samples, treatment with chemical reagents.